13C NMR of flavonoids-II: Flavonoids other then flavone and flavonol aglycones - Markham, K.R.; Ternai, B.
3C NMR spectra for a number of dihydroflavones, dihydroflavonols, flavans, chalcones, flavonols, an isoflavone and several glycosides in DMSO-d, solvent are reported and analysed. The use of established substitution additivity rules and '